Osteochondral Allograft Transplantation for the Unstable Capitellar Osteochondritis Dissecans Lesion: An Anconeus Preserving Approach - Aliya G. Feroe MD, MPH; Mark T. Langhans MD, PhD; Joaquin Sanchez-Sotelo MD, PhD; Mark E. Morrey MD; Christopher L. Camp MD (SAGE Publishing, 2023)
Background: Osteochondritis dissecans (OCD) of the capitellum can be a disabling condition that typically affects adolescent, overhead athletes. To date, a variety of different surgical treatment options have been described. Indications: Surgical indications for osteochondral allograft transplantation (OCA) for capitellar OCD lesions include failure of nonsurgical management or prior surgery and unstable, full-thickness lesions of almost any size affecting both bone and cartilage. The anconeus preserving approach specifically provides wide access to nearly the entire capitellum and can be used for lesions in almost any location. Technique Description: The anconeus preserving approach for OCA utilizes the interval between the anconeus and the ulna. With the patient positioned supine and the elbow flexed on an arm table, an incision is made approximately 1 cm lateral to the olecranon and is carried down to the fascia. Electric cautery is used to dissect the interval between the ulna and the anconeus. The anconeus is elevated off the ulna and retracted laterally to expose the underlying joint capsule. An L-shaped capsulotomy is performed over the center of the capitellum, just proximal to the annular ligament of the radial head. A pin is placed into the center of the lesion, perpendicular to the capitellum. A cannulated reamer 0.5 mm smaller than the lesion is used to ream the lesion to a depth of approximately 5 mm. Depth measurements are taken at all 4 poles of the defect. About 3 cc of bone marrow aspirate harvest is then obtained from the ulna using a cannulated needle. The oscillating saw is used to cut the graft to size using the prior measurements. The bone marrow aspirate is placed onto the osseous side of the graft before the osteochondral graft is impacted into the recipient site. The capsulotomy is then closed, and the anconeus is repaired back to the ulna. Postoperatively, patients begin range of motion as soon as tolerated, initiate strengthening at 6 weeks, and initiate return-to-sport programming at 3 months. Results: Lesions treated with OCA typically demonstrate improvement in all outcome measures, including functional scores, graft incorporation, articular surface congruity, and return-to-sport. Complications and graft failure is rare. Discussion/Conclusion: OCA using an anconeus preserving approach is a reliable option for surgical management of unstable OCD lesions. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.